2000
DOI: 10.1038/sj.bmt.1702562
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathology or immunopathology? The puzzle of cytomegalovirus pneumonitis revisited

Abstract: Summary:Various hypotheses have been proposed to explain why cytomegalovirus pneumonitis (CMV-P) is frequent and severe in bone marrow transplant patients while remaining rare and mild in HIV infected patients. One hypothesis suggests that CMV-P is an immunopathological condition that is common in bone marrow transplantation (BMT) under the effects of an abnormally regenerating immune system that reacts against CMV infected lung tissue. Such a hypothesis implicates CD4 T lymphocytes as one of the critical cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 55 publications
0
42
0
3
Order By: Relevance
“…Since then, the literature on clinical CMV-IP has been filled with case reports that interpret single clinical observations in favor or disfavor of Grundy's immunopathogenesis hypothesis. Rebuttal came primarily from clinicians who outlined in detail that the immunopathological characteristics ascribed to mCMV pneumonia do not apply to most cases of hCMV pneumonia (4,29). Specifically, Morris (29) concluded that the murine model is not valid.…”
mentioning
confidence: 99%
“…Since then, the literature on clinical CMV-IP has been filled with case reports that interpret single clinical observations in favor or disfavor of Grundy's immunopathogenesis hypothesis. Rebuttal came primarily from clinicians who outlined in detail that the immunopathological characteristics ascribed to mCMV pneumonia do not apply to most cases of hCMV pneumonia (4,29). Specifically, Morris (29) concluded that the murine model is not valid.…”
mentioning
confidence: 99%
“…Interstitial pneumonia is a frequent manifestation of CMV disease with a high fatality rate after lung and heart-lung transplantation and after allogeneic BMT (6,38,54), suggesting that recurrent virus may directly originate from the lungs due to reactivating transcriptional signals induced by cellular stress conditions and/or cytokines associated with transplantation procedures and host-versus-graft or graft-versus-host immunological responses.…”
mentioning
confidence: 99%
“…Quantitative viral load is correlated with the development of end-organ-disease caused by cytopathic eVects following viral replication. However, HCMV associated disease may also occur due to indirect eVects of infection which are caused mostly by antiviral immunity of patients with low viral load (e.g., patients with septic shock) [2,49]. As outlined in this model, reactivation is stimulated independent from immunosuppression whereas the grade of viral dissemination (viral load) and the risk of end-organ-disease are inXuenced by the immune status of the host.…”
Section: Disease Caused By Direct and Indirect Evectsmentioning
confidence: 98%
“…The indirect eVects of HCMV infection are very heterogeneous and even less characteristic from the clinical point of view [2,49]. The diagnosis of indirect eVects is diYcult to achieve because clear-cut criteria are missing.…”
Section: Disease Caused By Direct and Indirect Evectsmentioning
confidence: 99%